Children with autism are impaired in the understanding of teaching. Issue 2 (8th December 2015) - Knutsen, John; Mandell, David S.; Frye, Douglas
Abstract: Children learn novel information using various methods, and one of the most common is human pedagogical communication or teaching – the purposeful imparting of information from one person to another. Neuro‐typically developing (TD) children gain the ability to recognize and understand teaching as a core method for acquiring knowledge from others. However, it is not known when children with Autism Spectrum Disorder (ASD) acquire the ability to recognize and understand teaching. This study (total N = 70) examined whether children with ASD recognize the two central elements that define teaching: (1) that teaching is an intentional activity; and (2) that teaching requires a knowledge difference between teacher and learner. Theory of mind understanding was also tested. Compared to individually matched TD children, high cognitively functioning children with ASD were impaired in their comprehension of both components of teaching understanding, and their performance was correlated with theory of mind understanding. These findings could have broad implications for explaining learning in children with autism, and could help in designing more effective interventions, which could ultimately lead to improved learning outcomes for everyday life skills, school performance, health, and overall well‐being. Abstract : In this study we investigated the understanding of teaching in ASD. Compared to matched TD controls, children with ASD were impaired in their comprehension that teaching is an intentional activity that requires a knowledge difference between teacher and learner.